Effect of differences in kicking legs, kick directions, and kick skill on kicking accuracy in soccer players - Nagasawa, Y.; Demura, S.; Matsuda, S.; Uchida, Y.; Demura, T. (Journal of Quantitative Analysis in Sports, 2011)
It is important for soccer players to accurately kick a ball in various directions with both legs. This study aimed to examine the accuracy of the kick in soccer players in terms of kick direction, kicking legs (dominant and non-dominant legs), and experience. Methods: Seventeen male soccer players (age: 20.1 ± 1.1 yr) and fourteen male university students without soccer experience (age: 19.8 ± 1.2 yr) participated in the experiment. They kicked a ball from the penalty spot to the targets set at four corners of the goal and the accuracy of each kick was measured. Results: The soccer group`s score was significantly higher than that of the control group regardless of the kick direction or kicking legs. The score of the upper position targets was significantly lower than that of the lower position targets in both groups. There was no significant difference between the scores of the lower position targets of dominant and non-dominant legs in the soccer group. In addition, the score of reverse cross directions (kicking towards the right side of the goal with the right-leg) was significantly higher than that of cross directions (kicking towards the left side of the goal with the right-leg) in soccer players. Conclusion: Soccer players differ non-significantly between the dominant and non-dominant legs in the accuracy of inside kick with low trajectory and have high accuracy when kicking in the reverse cross direction.